2017
DOI: 10.1016/j.bbmt.2017.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of High-Dose Therapy and Autologous Stem Cell Transplantation for Mantle Cell Lymphoma: Effectiveness of Maintenance Rituximab

Abstract: High-dose therapy followed by autologous stem cell transplantation (ASCT) can improve outcomes for mantle cell lymphoma (MCL) but is associated with a high incidence of relapse. A retrospective study of 191 MCL patients who underwent ASCT at City of Hope was performed to examine prognostic factors for outcomes following ASCT. For all patients, the 5-year overall survival (OS) was 71% (confidence interval [CI]: 63% – 77%) and progression-free survival (PFS) was 53% (CI: 45% – 60%). The 5-year cumulative inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…While certainly a proof of concept, there is currently no wide-scale approach for measuring MRD in large numbers of patients, and these methods will require validation across more institutions. The absence of such a universal approach has prompted the investigation of maintenance rituximab to produce more durable long-term remissions post-ASCT 19 . The Nordic group first showed that pre-emptive treatment with four doses of rituximab at first sign of molecular relapse led to a re-induction of molecular remission in over 90% of patients 20 .…”
Section: Treatment Strategies In Fit Patientsmentioning
confidence: 99%
“…While certainly a proof of concept, there is currently no wide-scale approach for measuring MRD in large numbers of patients, and these methods will require validation across more institutions. The absence of such a universal approach has prompted the investigation of maintenance rituximab to produce more durable long-term remissions post-ASCT 19 . The Nordic group first showed that pre-emptive treatment with four doses of rituximab at first sign of molecular relapse led to a re-induction of molecular remission in over 90% of patients 20 .…”
Section: Treatment Strategies In Fit Patientsmentioning
confidence: 99%
“…[4] This study was one of the group dedicated to autotransplanted MCL patients. Other retrospective studies also suggested the potential benefits of chronic rituximab use in the post-transplant period [12,13,14]. There are also attempts to use other anti-CD20 monoclonal antibodies in maintenance therapy: ofatumumab and obinutuzumab, supported by quite promising results of preclinical studies [15,16].…”
Section: Discussionmentioning
confidence: 96%
“…As MCL is considered an incurable disease with frequent relapses, studies have focused on the use of maintenance therapy to prolong remission either post-induction or post-auto-HCT. While prior studies have shown the importance of maintenance with either rituximab or bortezomib post-auto-HCT [ 6 , 7 , 9 , 10 , 15 ], this trial is the first to study the combination in this setting. In this multicenter phase II prospective trial, we showed that the combination of rituximab and bortezomib as maintenance therapy post-consolidative auto-HCT is feasible, well tolerated, and yielded a 2-year DFS of 90.2%.…”
Section: Discussionmentioning
confidence: 99%
“…Rituximab, an anti-CD20 monoclonal antibody, has been shown to improve PFS as maintenance therapy in patients with MCL not undergoing auto-HCT [ 6 ] or undergoing auto-HCT [ 7 9 ]. Le Gouill et al showed in a randomized trial that rituximab maintenance can prolong PFS and overall survival (OS) in patients with MCL post consolidative auto-HCT [ 7 ].…”
Section: Introductionmentioning
confidence: 99%